Influencia de los factores de riesgo psicosociales en la salud mental. Cooperativa San José Limitada. Bolívar, 2021 - Chiriapa Solano, Estefanía Adriana (2022)
The aim of this research was to analyze the influence of psychosocial risk factors on mental health in the staff of Cooperativa San José Limitada, Bolívar, 2021. This was a bibliographic and field research with a cross-sectional, non-experimental and descriptive design. It was made up by a population of 170 workers, the psychometric instruments applied were the Psychosocial Risk Assessment Questionnaire and the Positive Mental Health Questionnaire. The results showed the presence of psychosocial risk factors with a higher influx of medium risk in the following dimensions: “recovery” with 62.94%, “workload and rhythm of work” with 52.35%, “support” with 48.82%, “action and control margin” with 48.23%; in mental health there was a medium level with 23.53% and a high level with 71.17%. Therefore, it is concluded that the study population has the presence of psychosocial risk factors with medium affluence in certain dimensions; and a mental health between medium and high levels. Based on the results obtained, the implementation of the proposed plan of psychological strategies is recommended in order to prevent psychosocial risk factors and maintain optimal mental health in workers.